Pengembangan Layanan E-mail dengan Model Webmail Multi Account - supadi -; I Made suparte (Jurnal Informatika, 2010)
E-mail is one of the Internet resources used to exchange information electronically. Derived from information  data retrieval survey of users e-mail, the result of internet users who ha ve more than one e-mail more than just a single e-mail account. The tendency of the owner of the e-mail that more than one to manage e-mail on an even keel is still a problem in implementation. This can be caused by the level of interest will e-mail is used. Another problem because the procedures for using e-mail that you have to login to some webmail is used. The research conducted was to develop an e-mail service that already exists to be integrated in a joint management by using a system called multi Webmail account. This system is an alternative solution for managing e-mail in a treatment procedure and in one view webmail. Development of system utilizing JavaScript and XML capabilities or commonly known as AJAX (Asynchronous JavaScript And XML). AJAX is a web-based programming techniques to create a web application more interactive and dynamic. Keyword : e-mail, Webmail Multi Account, Ajax